The Reconstruction Procedure Using Osteocutaneous Vascularzed Fibula Graft in Limb Salvage Surgery for Recurrence Adamantinoma of Tibia - Ade Martinus (Journal of Global Pharma Technology, 2017)
Introduction Adamantinoma is a very rare malignant bone tumor. The recurrence case seems to have more rapid enlarges and more aggressive invasion of surrounding soft tissue. Recently limb salvage has become the primary method of bone tumor treatment due to oncologist orthopaedic surgical advancement and more accurate imaging techniques. The osteocutaneous fibula graft is one of the advance option for intercalary reconstruction of the defect after bone tumor resection. The objectives of this case report are to present the reconstruction procedure of recurrence primary bone tumor using osteocutaneous fibular graft. Case Report.22 year’s old male with mass on right leg that gradually increased in size. He was previously diagnosed to have an adamantinoma, excised in other hospital 5 years ago. Radiograph and MRI examination support a recurrence adamantinoma of tibia and was confirmed by histopathologic result. Discussion we performed a limb salvage procedure via wide excision and reconstruction using osteocutaneous fibular graft. We were able to preserve the anterior tibial and posterior tibial neurovascular bundle. The recipient anterior tibial artery and vein was chosen to anastomose to donor vessels. The flap is vital and the patient discharged on 5th day. Conclusion: The limb salvage surgery with reconstruction procedure using osteocutaneous vascular zed fibula graft is a feasible surgical treatment in case of recurrence adamantinoma of tibia. Osteocutaneous fibula graft has been proven to be an ideal choice due to very high bony union rates, provide well-perfused bone, the capability of osteogenesis, and improved regional circulation. Keywords: Adamantinoma, Recurrence, Intercalary reconstruction, Osteocutaneous fibula graft, Limb salvage surgery.